Possibilities of the AutoCAD Program in Creating Electronic Textbooks for the Course "Engineering and Computer Graphics" - Dilfuza S. Umarova (Zien Journals, 2023)
This article provides examples to show that AutoCAD (Computer Aided Design (CAD)) has been and remains a powerful tool for technical graphics. Since Autodesk is a pioneer in the commercially available CAD market, Autodesk has developed CAD principles (which can be used by relatively untrained users), the nature and scope of commands, the sequence and specifics of their implementation. In terms of technical characteristics, AutoCAD is a complete tool that covers the entire range of functions in the area of the course "Engineering and Computer Graphics"
Keywords: CAD; education; engineering and computer graphics